1987
DOI: 10.1200/jco.1987.5.4.629
|View full text |Cite
|
Sign up to set email alerts
|

Sequential chemotherapy and radiation for nasopharyngeal cancer: absence of long-term benefit despite a high rate of tumor response to chemotherapy.

Abstract: Between April 1981 and December 1983, patients with locoregional carcinoma of the nasopharynx were treated with two courses of chemotherapy administered before radiation therapy. Chemotherapy consisted of methotrexate, bleomycin, and cisplatin, which were administered at 3-week intervals, and radiation therapy was scheduled to commence 3 weeks after the start of the second course. Forty-nine of 51 consecutive patients were treated; only one patient progressed on chemotherapy, and of 36 patients with measurable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(13 citation statements)
references
References 12 publications
3
10
0
Order By: Relevance
“…When response rates for NPC are compared to those obtained in recurrent squamous cell cancer of other head and neck sites, it seems that NPC is more likely to show an objective regression of neoplastic lesions both in our and others experience (Al Sarraf, 1988;Choksi et al, 1988;. A degree of responsiveness higher than that for other head and neck carcinomas has also been reported by some authors in studies dealing with previously untreated patients who received chemotherapy as initial treatment before locoregional therapy (Hill et al, 1986;Clark et al, 1987;Tannock et al, 1987;Bachouchi et al, 1990). However, in our opinion the mean duration of objective response to CDDP-based chemotherapy is far from optimal, and that of responses achieved with second line chemotherapy is dismal.…”
Section: Discussionsupporting
confidence: 69%
“…When response rates for NPC are compared to those obtained in recurrent squamous cell cancer of other head and neck sites, it seems that NPC is more likely to show an objective regression of neoplastic lesions both in our and others experience (Al Sarraf, 1988;Choksi et al, 1988;. A degree of responsiveness higher than that for other head and neck carcinomas has also been reported by some authors in studies dealing with previously untreated patients who received chemotherapy as initial treatment before locoregional therapy (Hill et al, 1986;Clark et al, 1987;Tannock et al, 1987;Bachouchi et al, 1990). However, in our opinion the mean duration of objective response to CDDP-based chemotherapy is far from optimal, and that of responses achieved with second line chemotherapy is dismal.…”
Section: Discussionsupporting
confidence: 69%
“…In the current study, a signi cantly high initial clinical response rate was obtained in 86% of patients with 44% complete responders. This overall response rate following induction CT is comparable to some series (4,10,20,23), but lower than that reported by others (19,21,22). This may re ect differences in administered doses and number of cycles as well as in the chemotherapeutic agents used.…”
Section: Sur×i×al and Disease -Free Inter×alsupporting
confidence: 73%
“…Data accumulated from numerous phase II trials showed that the use of neoadjuvant CT was associated with encouraging response rates ranging from 75 to 98% (19)(20)(21)(22). However, whether the excellent response to CT can be translated into survival bene t has not been determined (23)(24)(25). Several studies that used non-controlled historical data and matched cohort groups provided evidence that induction CT prior to de nitive radiation improves freedom from distant metastases, disease-free survival (DFS) and OS for patients with advanced disease (4,11,26).…”
Section: Discussionmentioning
confidence: 99%
“…Advanced T-stage and lower radiation doses predicted locoregional tumoral failure, whereas advanced N-stage and exclusion of chemotherapy predicted systemic failure. The relatively short time to development of systemic failure, in the absence of locoregional tumoral failure, might indicate the presence of occult systemic disease at the time of diagnosis [27,41,42].…”
Section: Discussionmentioning
confidence: 97%